Emerging Roles of Circ-ZNF609 in Multiple Human Diseases - Wang, Songbo; Wu, Jiajin; Wang, Zhongyuan; Gong, Zixuan; Liu, Yiyang; Wang, Zengjun (Frontiers in Genetics, 2022)
Circular RNAs are a special type of endogenous RNAs with extensive roles in multiple human diseases. They are formed by back-splicing of partial sequences of the parental precursor mRNAs. Unlike linear RNAs, their covalently closed loop structure without a 5’ cap and 3’ poly-adenylated tail, confers on them high stability and difficult to be digested by RNase R. Increasing evidence has proved that aberrant expressions of many circRNAs are detected and exert essential biological functions in diseases development and progression via acting as a molecular sponge of microRNA, interacting with proteins as decoys or scaffolds, or self-encoding small peptides. Circular RNA zinc finger protein 609 (circ-ZNF609) originated from exon2 of ZNF609, which is located at chromosome 15q22.31 and recently proved can translate into protein. Aberrantly upregulated in various diseases, it could promote malignant progression of human tumors, as well as tumor cell proliferation, migration, and invasion. Here in this review, we concluded the biological functions and potential mechanisms of circ-ZNF609 in multiple diseases, which could be further explored as a targetable molecule in future accurate diagnosis and prognosis.